El principio de superposición de estados, a partir de los estados de polarización de una onda monocromática - Mendoza Cely, Diana Milena; Rozo Clavijo, Mauricio (Revista Científica, 2011)
A reflection on the principle of superposition of states is presented, from the analysis of the concept of state within the context of classical mechanics and quantum mechanics context. Also, it aims to examine how it implements the idea of superposition, based on the analysis of states of polarization of a monochromatic wave. The principle of superposition of states is one of the fundamental principles of quantum mechanics, has a degree of difficulty among students, it is not mediate understand that a system can be in a state as a linear combination of other states. In this way, analogies are used as a teaching tool within the context classical and quantum, to conceptualize and establish the principle of superposition differences from the classical theory and quantum theory.